2023
DOI: 10.1038/s41699-023-00394-0
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring the dielectric screening in WS2–graphene heterostructures

Abstract: The environment contributes to the screening of Coulomb interactions in two-dimensional semiconductors. This can potentially be exploited to tailor material properties as well as for sensing applications. Here, we investigate the tuning of the band gap and the exciton binding energy in the two-dimensional semiconductor WS2 via the external dielectric screening. Embedding WS2 in van der Waals heterostructures with graphene and hBN spacers of thicknesses between one and 16 atomic layers, we experimentally determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…In our laboratory, the method has been widely adapted, with more than 10 6 images taken within 24 months by over 30 individual researchers and supporting several projects [47][48][49]. Our implementation not only speeds up sample fabrication for individuals, but has proven to have synergies in a group working on 2D materials, as exfoliated materials can be easily shared between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…In our laboratory, the method has been widely adapted, with more than 10 6 images taken within 24 months by over 30 individual researchers and supporting several projects [47][48][49]. Our implementation not only speeds up sample fabrication for individuals, but has proven to have synergies in a group working on 2D materials, as exfoliated materials can be easily shared between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrate the capability of the setup by acquiring a hyperspectral PL and RC image of a TMD monolayer sample at room temperature; further RC measurements taken with the setup can be found in the study of reference [13]. The sample is a MoSe 2 -WSe 2 in-plane heterostructure grown by chemical vapor deposition using the one-pot chemical vapor deposition growth method [25].…”
Section: Pl Imaging Of Lateral Heterostructuresmentioning
confidence: 99%
“…(gate-defined) nano-scale potentials for exciton confinement [10,11], or heterostructures of different materials or stacking orders [12,13] as well as for material-specific inhomogeneities, such as strain, charge and screening-induced disorder [14][15][16] or localized defects [17].…”
Section: Introductionmentioning
confidence: 99%
“…22 For device applications, typically hBN multilayer flakes are used either as an insulating and optically transparent capping layer or as smooth support for exfoliated TMD monolayers, while hBN monolayers are mainly used as an insulation layer between 2D materials, where its roughness does not have a major influence. 23 In contrast, the optical peculiarity of TMD monolayers requires the explicit use of monolayers for the preparation of defined organic/TMD hybrid systems, e.g., to investigate optical coupling phenomena. This seems to be more challenging because 2D monolayers often exhibit the phenomenon of wrinkling, 24,25 whose influence on the subsequently grown molecular adlayers has not yet been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…There, it was found that thin exfoliated and transferred (multilayer) flakes often exhibit reduced surface quality and increased density of defects (e.g., steps), which affect the ordering of subsequently grown molecular films and result in coexisting defect-driven molecular film structures with different molecular orientations . For device applications, typically h BN multilayer flakes are used either as an insulating and optically transparent capping layer or as smooth support for exfoliated TMD monolayers, while h BN monolayers are mainly used as an insulation layer between 2D materials, where its roughness does not have a major influence . In contrast, the optical peculiarity of TMD monolayers requires the explicit use of monolayers for the preparation of defined organic/TMD hybrid systems, e.g., to investigate optical coupling phenomena.…”
Section: Introductionmentioning
confidence: 99%